Proceedings of the 2017 International Conference on Organizational Innovation (ICOI 2017) 2017
DOI: 10.2991/icoi-17.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and Staff Turnover Intentions in Private Hospitals

Abstract: Abstract-The purpose of this study is to examine the correlation of organizational justice, supervisor-employee relationship, and job satisfaction to nurse' turnover intentions in private hospitals. A survey study with a total of 152 nurses from two hospitals. Technique of taking data using closed questionnaire. Data analysis using structural equation modeling. Organizational justice and supervisor-employee relationship have direct effect on job satisfaction, and influence nurse's intentions turnover either di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
3
1
2
Order By: Relevance
“…However, TSR in our study was lower than the reported range of 81%-99% from Nigeria, Saudi Arabia, Pakistan, and Ethiopia [24][25][26][27]. The lower TSR figures may be due to the high turnover of staff trained on DOTS which was not uncommon with the private sector [28]. Private sector staffs in Nigeria were poorly paid, and they combined multiple clinical and administrative roles in the hospitals; hence the enormous workload facilitated their constant job hunting.…”
Section: Discussioncontrasting
confidence: 78%
“…However, TSR in our study was lower than the reported range of 81%-99% from Nigeria, Saudi Arabia, Pakistan, and Ethiopia [24][25][26][27]. The lower TSR figures may be due to the high turnover of staff trained on DOTS which was not uncommon with the private sector [28]. Private sector staffs in Nigeria were poorly paid, and they combined multiple clinical and administrative roles in the hospitals; hence the enormous workload facilitated their constant job hunting.…”
Section: Discussioncontrasting
confidence: 78%
“…The results of this study are supported by the results of previous relevant research conducted by Pelamonia (2019), that leadership, among others, affects employee performance. The same thing is also shown from the results of Kuntardina's research (Kuntardina, 2017), which states that organizational justice and supervisor-employee relationships affect nurses' intentions to change their jobs.…”
Section: The Effect Of Organizational Commitment On Turnover Intentionmentioning
confidence: 53%
“…Hal ini berarti adanya turnover intention yang tinggi tidak hanya disebabkan organizational justice yang rendah namun juga pada rendahnya kepuasan kerja yang dirasakan karyawan. Hasil penelitian ini mendukung penelitian (Suifan et al 2017;Kuntardina, 2017).…”
Section: Tabel 6 Hasil Pengujian Hipotesis Pengaruh Langsungunclassified
“…Penelitian sebelumnya menunjukkan bahwa organizational justice memiliki pengaruh pada sikap dan perilaku karyawan di tempat kerja seperti kepuasan kerja dan akhirnya pada turnover intention. Oleh karenanya, kepuasan kerja sangat penting dalam memediasi dalam hubungan organizational justice dan turnover intention (Suifan, Diab, dan Abdallah, 2017;Kuntardina, 2017).…”
unclassified